Tagmem pada Frasa Keripik Pisang dan Frasa Nasi Tiwul (Kajian Tagmemik) - Yeni Utami; Hasan Busri; Akhmad Tabrani (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
Apart from having an eclectic, universal nature, Tagmemik studies can also be used to analyze language such as the phrases "banana chips" and "tiwul rice". So, the aim of this research is to describe the tagmemes in the phrase banana chips and describe the tagmemes in the phrase nasi tiwul. This research method uses a qualitative research approach and descriptive research type. The researcher's presence will be in May, June 2024. The research setting is this research. The research data is language in the form of banana chips phrases and tiwul rice phrases. The research data source is a researcher who lives in Punung subdistrict, Pacitan district with the name Yeni Utami. Secondary data sources are Mrs. Suparni who has made tiwul rice, Mrs. Suwatmi who sells tiwul rice at the Margo Mulyo Punung market, the internet pacitanku.com, and prabangkanews.com as sources for the phrase tiwul rice while the secondary source for the phrase banana chips is the written language of banana chips "sweet crunchy" Mrs. Sri Wahyuni ​​Pagutan, Pringkuku, Pacitan. The data collection procedure is by listening through field observations and internet observations. Then also use advanced note-taking techniques by using the data as the research object in the title. Data analysis technique by connecting tagmem theory with the data or research object stated in the title, namely banana chips and tiwul rice. Data validity techniques using theory triangulation and research method triangulation. Presentation of data using ordinary or formal language. The results of the research describe how slot, class, role, and cohesion are in the phrase "banana chips" and the phrase "tiwul rice" and the result is that it is true that a phrase is a noun phrase. Each phrase "banana chips" and the phrase "tiwul rice" in the slot section has a core and extra-core function. The class dimension has the form of basic morphemes, nouns, and has a subclass of noun phrases. The dimension of the role as a perpetrator or sufferer which has a function as a subject with the role of sufferer. The cohesion dimension can function as a filler for clauses that are transitive, intransitive or equative. Both as fillers for subject and object clauses. Suggestions for further research are that language researchers should use research objects in the form of data on phrases or clauses that are commonly used in everyday life, whether culinary, cultural, religious and social. So, research directly examines the language or uses research objects in the form of language.